A COMPARATIVE STUDY ON EXTRACTION AND CHARACTERIZATION OF MELON ( C ucumis melo) SEED OIL AND ITS APPLICATION IN BAKING - Z. Ahmad; M. Rafay; M. R. Shaheen; M. S. Javed; O. M. Tarar; M. R. Tariq; M. A. Nasir (Journal of Animal and Plant Sciences, 2019)
Melon (Cucumis melo) seeds are rich source of oil, protein and possess numerous medicinal properties; however, these are normally treated as waste. Present study was conducted to characterize the melon seed oil and to assess its potential to improve bread quality characteristics. For the purpose melon seed oil was extracted, analyzed regarding different parameters and utilized in bread manufacturing at various concentrations (T0=5% Shortening (control), T1=4 % melon seed oil, T2=5 % melon seed oil, T3= 6 % melon seed oil, T4=7 % melon seed oil). The results showed that melon seeds contain 29.86% oil. Iodine and saponification values were found as 118.8±3.57 (mg Iodine g -1), 188.83±5.37 (mg KOH g -1) respectively. Fatty acid profile revealed that linoleic acid was found in higher concentration i.e. 62.95g/100g.  The oleic acid, palmitic acid, steric acid and cis-5, 8, 11, 14, 17 eicosapentanoic acid methyl esters were present in concentrations of 20.35, 4.96, 3.01 and 1.89g/100g, respectively. It was found, the melon seed oil improved bread quality characteristics like volume, relative volume, specific volume and density when it was applied at the level of 5% (T2). It improved sensory attributes of bread samples with the best results produced by T2.
Keywords: Melon seed oil; Fatty acid profile; Bread quality; Volume; Sensory evaluation